IMPLEMENTASI KURIKULUM BAHASA ARAB DI PTKIS - Abdurrahman Abdurrahman (Jurnal Penelitian Ilmiah INTAJ, 2018)
Arabic language education has become one of the subjects in all programs of faculties in Islamic Universities (PTKIS), especially in 154 Universities under the supervision of the fourth Coordinator for Islamic Universities, (Kopertais IV). However, the phenomenon of communicative foreign language learning (PBAK) according to the KTSPT 2009 was not directed at achieving the five competencies of the Kepmendiknas Regulation No. 045 (2002), for the clustering of certain subjects in the independent subjects. This leads to reduce graduate degree competence. This paper was presented in particular in the future approaches to curriculum building through the competency based the Indonesian Qualifications Framework (KBK KKNI) in accordance with the Presidential decree No. 8 (2012) by setting the communicative scope in teaching Arabic as an approach to achieve all five competencies together. The first possible plan for this purpose is to make use of the Language Center (LC) in two plans. First reforming the status of the language center, and secondly delegating subjects from college faculties to language center.